2017
DOI: 10.1080/13647830.2017.1333157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stoichiometry on premixed flames propagating in narrow channels: symmetry-breaking bifurcations

Abstract: Recent studies within the diffusive-thermal (constant-density) approximation have shown that, for premixed flames freely propagating in narrow adiabatic channels, the instabilities induced by differential diffusion may result in non-symmetric solutions and/or oscillating and rotating propagation modes. This has been shown in the context of lean mixtures, for which a single species transport equation with a single Lewis number (corresponding to the ratio of thermal to molecular diffusivity of the deficient reac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…with the Zel'dovich number defined as β = E(T a −T u )/(RT 2 a ). The factor s L = (S L )/(S L ) asp = 1.05 is the eigenvalue of the planar adiabatic problem [5], where the propagation velocity S L for finite β is compared with the propagation velocity for infinitely-large activation energy (S L ) asp .…”
Section: Scales and Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…with the Zel'dovich number defined as β = E(T a −T u )/(RT 2 a ). The factor s L = (S L )/(S L ) asp = 1.05 is the eigenvalue of the planar adiabatic problem [5], where the propagation velocity S L for finite β is compared with the propagation velocity for infinitely-large activation energy (S L ) asp .…”
Section: Scales and Governing Equationsmentioning
confidence: 99%
“…The study of the propagation of premixed-gas flames in narrow chambers is key to understand most of these phenomena, which are typically enhanced by the geometrical restraint of the flow. Experimental, theoretical and numerical efforts have been instrumental in providing insight on the flame shape [5,6], the propagation rate [7][8][9] and the flame stability under various conditions and regimes [5,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1 with a dash-dot line. The possible impact of non-symmetric flames similar to those reported in [20][21][22][23] is out of the scope of the present study and will be reported elsewhere.…”
Section: General Formulationmentioning
confidence: 68%
“…In this expression, which implies that u 0 = − 1 3 dp 0 /dx, the function dp 0 /dx is as yet unknown but can be determined by using (17) after averaging it, as is classically done in lubrication theory; hence…”
Section: Asymptotic Analysismentioning
confidence: 99%
“…Since its introduction, the thick flame asymptotic limit has been adopted in studies by various workers and has gained some popularity partially due to an emerging interest in micropower generation using combustion [12]. Several aspects of thick flames have thus been investigated to date including the effect of heat loss and preferential diffusion [7,11,13], the effect of gas expansion [2,14,15], and flame stability [16,17]. The reader is referred to these publications and references therein for a proper account regarding these aspects.…”
Section: Introductionmentioning
confidence: 99%